sin(π/6+x)=1/3 cos(2π/3-2x)=?
1个回答
cos(π/3-x)
=sin[π/2-(π/3-x)]
=sin(π/6+x)
=1/3
所以cos(2π/3-2x)
=cos[2(π/3-x)]
=2cos²(π/3-x)-1
=-7/9
相关问题
为什么cos(2x-π/3)-sin(5π/6) =cos(2x-π/3)?
1、sin[(π/6)-x]=1/3,则cos[(2/3π)+2x]=?
sin(x+π/6)=1/2,则cos(π/3-x)
已知f(x)=sin(x−3π)•cos(2π−x)•sin(−x+3π2)cos(−x−π)•cos(π2−x)
已知sin(x+π/3)=1/4,求sin(2π/3-x)+cos²(π/6-x)
已知 f(x)= sin(x-3π)•cos(2π-x)•sin(-x+ 3π 2 ) cos(-x-π)•cos( π
设函数f(x)sin(x+π/3)+2sin(x+π/3)-根号3cos(2π/3-x) (1)求f(π/6),f(π/
若sin(x-π)=2cos(2π-x),求(sin(π-x)+5cos(2π-x))/(3cos(π-x)-sin(-
求函数y=[sin2x+sin(2x+π/3)-cos1/2﹙π-4x﹚]/[cos2x+cos﹙2x+π/3﹚-sin
1.y=sin(1/2x+π/6),x属于[0,π/3] 2.y=-cos(3x-π/3),x属于[-π/3,π/3]